Setting Komunikasi Café Pancong Balap Teduh Purwakarta - Muhammad Adrian Rosyid; Yulianti (UNISBA Press, 2023)
Abstract. There is a change in traditional culinary that has survived its presence in today's thriving international cuisine. There is a unique cafe that sells pancong cakes, this cafe is called Cafe Pancong Balap Teduh. The purpose of this study was to find out how the communication setting of Café Pancong Balap Teduh is. With qualitative research methods using a case study approach. Data collection techniques used are interviews, observation, and literature study. Interviews were conducted with the owners of Café Pancong Balap Teduh, namely Anjar Gutama, Rifky Dwi Adi, and Muhammad Adrian Daffa. The results of the study show that Café Pancong Balap Teduh has the latest concept of space, which is changing the concept of a coffee shop to the concept of Coffee and Space. The concept of time for Café Pancong Balap Teduh with a new concept, and new operational hours, which is open every day starting at 15.15 – 23.00 WIB. The Physical Concept of Café Pancong Balap Teduh performs the physical concept in a neat and complete manner so that visitors know that it is currently a coffee and space concept. Café Pancong Balap Teduh chose the name pancong as the name of the café because it wanted to communicate that the hallmark of this café is selling pancong cake as the main menu where pancong cake is a traditional cake that is rarely found. Abstrak. Terdapat perubahan kuliner tradisional yang bertahan kehadirannya dalam masakan internasional yang berkembang saat ini. Terdapat sebuah kafe unik yang menjual kue pancong, kafe ini bernama Cafe Pancong Balap Teduh. Tujuan penelitian ini adalah untuk mengetahui bagaimana setting komunikasi Café Pancong Balap Teduh. Dengan metode penelitian kualitatif menggunakan pendekatan studi kasus. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan studi kepustakaan. Yang dilakukan wawancara kepada owner Café Pancong Balap Teduh yaitu Anjar Gutama, Rifky Dwi Adi, dan Muhammad Adrian Daffa. Hasil penelitian menunjukan Café Pancong Balap Teduh terdapat Konsep ruang terbaru yaitu merubah konsep kedai warung kopi menjadi konsep Coffee and Space. Konsep waktu Café Pancong Balap Teduh dengan konsep baru, dan jam operational baru yaitu buka setiap hari mulai pukul 15.15 – 23.00 WIB. Konsep Fisik Café Pancong Balap Teduh melakukan konsep fisik secara rapih dan lengkap agar pengunjung tau bahwa saat ini berkonsep coffee and space. Café Pancong Balap Teduh memilih nama pancong sebagai nama café karena ingin mengkomunikasikan bahwa ciri khas dari café ini adalah menjual kue pancong sebagai menu utama yang dimana kue pancong adalah kue traditional yang sudah jarang ditemukan.